An Improvement of the Palladium-Catalyzed [4+2] Cycloaddition of o-(Silylmethyl)benzyl Carbonates with Alkenes - Jin, Yushu; Ishizuka, Kentaro; Kuwano, Ryoichi (Synlett, 2014)
The palladium complex, which is generated in situ from Pd(η3-C3H5)Cp and tris(4-methoxy-3,5-dimethylphenyl)phosphine, catalyzed the [4+2] cycloaddition of o-(silylmethyl)benzyl carbonates with alkenes. The reaction of the benzyl esters with methyl crotonate gave methyl 3-methyltetralin-2-carboxylate in 84% yield with 2% catalyst loading.
Keywords: catalysis; cycloaddition; o-quinodimethanes; alkenes; palladacycles